Government Financial Performance Analysis - Novita Nugraheni; Yudhi Prasetiyo; Shufia Zuhroh; Etik Ipda Riyani (International Journal of Business and Applied Economics, 2023)
The aim of this research is to find out the performance of the central government using the value for money method. Measurement of financial performance is useful as a periodic government report in evaluating the level of effectiveness and efficiency of an organization in monitoring estimated costs with actual costs as well as as a tool for monitoring and evaluation materials of the organization. One of the tools in measuring government performance is using value for money. The object of this research is the Ministry that exists in Indonesia with a total sample obtained by 23 Ministries. This study is a quantitative descriptive study. The results of this study are the Economic Ratio for 2020 with economic results. In 2021, with economic outcomes. Efficiency ratio for 2020 with fairly efficient results. In 2021, the results are inefficient. Efficiency ratio in 2020 with very effective results. In 2021, with very effective results. Implications of this research to various parties especially to governments and regulators for the formulation of public policy in the central government environment.